PS33 Health-Seeking Behaviour in the Era of Free Healthcare in Urban Slums in Sierra Leone. (17th September 2012) - Nathaniel-Wurie, L; Martin, G; Cooper, G; Bernier, G-L De; Ajayi, T; Martineau, F; Cridford, B; Lako, S
Abstract : Background: Sierra Leone has child health statistics which are amongst the worst in the world. In April 2010, the Government of Sierra Leone launched a Free Health Care Initiative (FHCI), eliminating user fees in government facilities for children under the age of five, as well as pregnant and lactating women. Data from Ola During Children's Hospital (ODCH), the country's only government-run tertiary paediatric hospital, suggests that the FHCI has increased service utilisation. However, mortality rates remain high and delayed presentation is a major factor contributing to poor outcomes. This study sought to understand health-seeking behaviour in the era of Free Health Care, as a means of addressing barriers to the delivery of timely paediatric care for the urban poor. Methods: Data was collected via focus group discussions and key informant interviews in Freetown. Men and women with at least one child below the age of five under their care were included. Participants were selected from neighbourhoods in Freetown where Ola During Children's Hospital (ODCH) represented the nearest secondary care facility to their usual place of residence. Focus groups were facilitated in Krio, the national language, guided by a pre-designed survey tool. Discussions were audio-recoded, transcribed and translated into English. Data analysis was conducted by the research team using a thematic framework. Results: Preliminary analysis reveals several factors contributing to delays in accessing appropriate care for sick children: Indirect costs: Transportation, child-minding, lost income, cost of prescribed medicines and unsanctioned charges for care that continue to be levied. The negative perceptions of ODCH staff and facilities: Perceived disrespectful, discriminatory or unfair treatment within the health facility. Numerous healthcare options more easily accessible: Private pharmacies, self-treatment at home using traditional (herbal) or allopathic remedies. Poor insight into disease: Deficiencies in caregivers' ability to recognise at what time during illness progression seeking healthcare would result in the highest cost benefit ratio. Non caregiver factors: Long queues, perceived complicated referral process between FHC facilities, and reduced opening hours. Conclusion: User fees represent a major barrier to accessing timely and appropriate care for poor children. However, the elimination of official charges for paediatric care in Sierra Leone has brought to the surface several critical factors, beyond direct costs, which also impact upon healthcare utilisation. Understanding the processes and determinants which modulate health seeking behaviour is fundamental to efforts to improve health outcomes for the most vulnerable children.